2018
DOI: 10.1016/j.ejvs.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Graduated Elastic Compression Stockings in Patients with Symptomatic Varicose Veins: A Randomised Double Blind Placebo Controlled Trial

Abstract: Among patients with varicose veins, GECS seem effective in ameliorating symptoms, particularly pain or aching, compared with placebo stockings after 1 week of use. Long-term studies are justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In 2018, an interesting randomized double-blind placebo-controlled trial demonstrated that 18-21 mmHg GCS are able to positively impact pain and aching related to venous disease. 130 In this context, it should be remembered that subjective symptoms are not specific for venous changes and they can also by improved by GCS. 131 An increasing scientific interest is dedicated to the evaluation of the GCS ability of potentially impacting sport performance and recovery.…”
Section: Long Distance Flights In 2011 British Journal Ofmentioning
confidence: 99%
“…In 2018, an interesting randomized double-blind placebo-controlled trial demonstrated that 18-21 mmHg GCS are able to positively impact pain and aching related to venous disease. 130 In this context, it should be remembered that subjective symptoms are not specific for venous changes and they can also by improved by GCS. 131 An increasing scientific interest is dedicated to the evaluation of the GCS ability of potentially impacting sport performance and recovery.…”
Section: Long Distance Flights In 2011 British Journal Ofmentioning
confidence: 99%
“…Additionally, another randomized crossover trial on compression hosiery worn by hairdressers reported reduced discomfort, oedema, and pain in the legs [ 4 ]. Another study compared the use of compression stockings with non-compression stockings in patients with varicose vein symptoms and demonstrated that compression stockings were effective for pain but not for oedema or paraesthesia [ 15 ]. On the basis of these experimental studies, systematic reviews have been conducted on the effects of compression stockings on oedema risk and pain in healthy adults, which include the prevention and treatment of chronic venous disease, varicose ulcers, and deep venous thrombosis and treatment of lymphoedema [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have compared pressure intensity [ 16 , 17 ], with the majority comparing pressure stockings with placebo stockings [ 3 , 15 ]. Most studies incorporating different lengths of compression stockings examined the prevention of deep vein thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Compression therapy is the most widely used treatment method for preventing adverse effects of chronic venous disease (CVD) [ 1 , 2 ]. CVD, including varicose veins and chronic venous insufficiency, affects the quality of life of many individuals around the world [ 1 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The accurate interface pressure measurement is considered as one of the most challenging tasks faced in the fields of medical and biomedical engineering. Its importance also extends to fields like sports science, management of diabetes-related ulcers, prosthetics, and human joint studies [ 2 , 3 , 4 , 5 , 6 ]. The measurement of the interface pressure applied by the compression devices (bandage systems, stockings) are required for reasons such as the efficiency of the compression therapy product for the treatment of venous disease, to evaluate the applied pressure by medical compression bandages to improve the training of the bandaging technique, to design better compression systems and also to study the effect of different postures of patients on the applied pressures.…”
Section: Introductionmentioning
confidence: 99%